Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.bbrc.2018.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42-dependent modulation of rigidity sensing and cell spreading in tumor repopulating cells

Abstract: Recently, a robust mechanical method has been established to isolate a small subpopulation of highly tumorigenic tumor repopulating cells (TRCs) from parental melanoma cells. In order to characterize the molecular and mechanical properties of TRCs, we utilized the tension gauge tether (TGT) single-molecule platform and investigated force requirements during early cell spreading events. TRCs required the peak single molecular tension of around 40 pN through integrins for initial adhesion like the parental contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
3
7
1
Order By: Relevance
“…Based on this, we seeded single B16F1 melanoma cells in 90 Pa soft 3D fibrin gels. The majority of the cells do not survive the soft 3D microenvironment, which is consistent with published reports [ 14 , 16 , 17 , 18 ]. We tracked and imaged single cells up to 5 days ( Figure 1 b).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Based on this, we seeded single B16F1 melanoma cells in 90 Pa soft 3D fibrin gels. The majority of the cells do not survive the soft 3D microenvironment, which is consistent with published reports [ 14 , 16 , 17 , 18 ]. We tracked and imaged single cells up to 5 days ( Figure 1 b).…”
Section: Resultssupporting
confidence: 92%
“…Established cell lines, such as parental B16F1 cells, are traditionally cultured on tissue 2D culture treated rigid dishes. Previous studies, including our own, demonstrated that 3D fibrin gel of 90 Pa stiffness promotes the growth and selection of multicellular TRC spheroids [14,[16][17][18]. Growing evidence also reports similar findings that physical properties of the cellular microenvironment, such as stiffness, have an important role in promoting tumorigenic cancer cell growth [26,27].…”
Section: Growth and Selection Of Trc Spheroids By 90 Pa Stiffness 3d supporting
confidence: 75%
See 2 more Smart Citations
“…Both CDC42 and CDH5 knockdowns significantly reduce the spatial coordination of cell density, reflecting the importance of such coordination in collective cell migration. However, the depletion of these genes affects different mechanisms; the disruption of cell adhesion through CDH5 knockdown reduces cellular tension, while CDC42 knockdown affects cell response to microenvironmental change [35] , [36] . By considering multiple LCD-based measures we can discriminate among the different effects of these perturbations ( Fig.…”
Section: Discussionmentioning
confidence: 99%